Survival improvement in patients with non–small cell lung cancer between 1983 and 2012: Analysis of the Surveillance, Epidemiology, and End Results database. Issue 5 (April 2017) - Wang, Shuncong; Sun, Tiantian; Sun, Huanhuan; Li, Xiaobo; Li, Jie; Zheng, Xiaobin; Mallampati, Saradhi; Sun, Hongliu; Zhou, Xiuling; Zhou, Cuiling; Zhang, Hongyu; Cheng, Zhibin; et al.
Non–small cell lung cancer is the most common malignancy in males; it constitutes the majority of lung cancer cases and requires massive medical resources. Despite improvements in managing non–small cell lung cancer, long-term survival remains very low. This study evaluated survival improvement in patients with non–small cell lung cancer in each decade between 1983 and 2012 to determine the impact of race, sex, age, and socioeconomic status on the survival rates in these patients. We extracted data on non–small cell lung cancer cases in each decade between 1983 and 2012 from the Surveillance, Epidemiology, and End Results registries. In total, 573, 987 patients with non–small cell lung cancer were identified in 18 Surveillance, Epidemiology, and End Results registry regions during this period. The 12-month relative survival rates improved slightly across three decades, from 39.7% to 40.9% to 45.5%, with larger improvement in the last two decades. However, the 5-year-relative survival rates were very low, with 14.3%, 15.5%, and 18.4%, respectively, in three decades, indicating the urgency for novel comprehensive cancer care. In addition, our data demonstrated superiority in survival time among non–small cell lung cancer patients of lower socioeconomic status and White race. Although survival rates of non–small cell lung cancer patients have improved across the three decades, the 5-year-relative survival rates remain very poor. In addition, widening survival disparities among the race, the sex, and various socioeconomic status groups were confirmed. This study will help in predicting future tendencies of incidence and survival of non–small cell lung cancer, will contribute to better clinical trials by balancing survival disparities, and will eventually improve the clinical management of non–small cell lung cancer.